HUBUNGAN ANTARA KESEJAHTERAAN PSIKOLOGIS DENGAN KEPUASAN KERJA GURU TK DI SE-KECAMATAN BATU HAMPAR KABUPATEN ROKAN HILIR - Lestari Kurnianti; Rita Kurnia; Zulkifli N Zulkifli N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the correlation between psychological well-being and job satisfaction of the teachers at kindergarten in the Batu Hampar sub district Rokan Hilir. The population of this study is about 50 kindergarten teachers in the Batu Hampar sub-district. This study used quantitative correlation to determine the correlation between the independent and dependent variables. Data collecting technique used questioners on likert scale. The result of the test was analyzed by using likert scale trial through IBM SPSS (statistical package for social science) version 2o. From the analysis, it was showed that there is a positive correlation between psychological well-being and job satisfaction of the teachers at kindergarten in the Batu Hampar sub district Rokan Hilir. It can be seen from the correlation coefficient rxy= 0.486 with significance 0.000<0.05. The category is average with determinant coefficient KD= r2 x 100% = 0.486 x 100%= 23.62% it is mean that psychological well-being influences about 23.62 % to the teachers’ job satisfaction.Key Word: kindergarten’s teachers psychological well-being and kindergarten’s teachers job satisfaction